MONITORING GROUNDWATER CHEMICAL COMPOSITION AT A EXPERIMENTAL AREA IRRIGATED WITH PETROLEUM PRODUCED WATER - Stein, Paula; Melo Júnior, Germano; Cunha de Souza, Laécio (Geochimica Brasiliensis, 2019)
Agricultural reuse of the produced water is an efficient means for water resource management. However it is a potentially impacting activity to soil and groundwater, and thus requires environmental monitoring throughout the process. From this perspective, the present work aims at the monitoring of groundwater quality of karstic aquifer, located in the northeast of Brazil, where an irrigation experiment was carried out using PW of the Fazenda Belém oil field, in Ceará State, Brazil. Twelve monitoring wells were evaluated through a four-stage sampling program: the first before the installation of the irrigation experiment (CHA) and the other three, respectively, during (MO1), immediately at the end (MO2) and after the experiment (MO3). The climatic effect was also considered in the evaluation, since sampling events occurred in distinct seasonal periods: the first and the last at the end of the dry season and the second and third at the end of the wet season. Investigations were performed considering two groups of wells: upstream wells and downstream wells in relation to groundwater flow in the experimental area. For Ca2+, Mg2+, K+, total hardness, HCO3-, F-, As, B, Li and P, there was a tendency of increasing concentrations in the Monitoring sampling, in relation to CHA. However, since this scenario was verified in both sets of wells (upstream and downstream), its causes are probably related to natural factors. It was also observed that highest concentrations occur predominantly in the MO1 and MO2 sampling stages, that is, under the influence of the wet season, when water recharges promote dissolution of carbonate constituents present in the aquifer, thus increasing its dissolved concentration. Organic substances analyzed in groundwater were not detected or were detected at very low and dispersed concentrations and without any source specific signatures. Hence, their origin can be attributed to natural or diffuse inputs.